Erythropoietin Produces a Dual Effect on Carotid Body Chemoreception in Male Rats - Arias-Reyes, Christian; Laouafa, Sofien; Zubieta-DeUrioste, Natalia; Joseph, Vincent; Bairam, Aida; Schneider Gasser, Edith M.; Soliz, Jorge (Frontiers in Pharmacology, 2021)
Erythropoietin (EPO) regulates the ventilatory response to normoxia and hypoxia by interacting with the respiratory centers of the brainstem. Here we show, in isolated “en block” carotid body (CB) preparations containing the carotid sinus nerve (CSN) from adult male Sprague Dawley rats, that EPO acts as a stimulator of CSN activity in response to hypoxia at concentrations below 0.5 IU/Ll. Under hypercapnic conditions, EPO did not influence the CSN response. EPO concentrations above 0.5 IU/mL decreased the response of the CSN to both hypoxia and hypercapnia, reaching complete inhibition at 2 IU/mL. The inhibitory action of high-dose EPO on the CSN activity might result from an increase in nitric oxide (NO) production. Accordingly, CB preparations were incubated with 2 IU/mL EPO and the unspecific nitric synthase inhibitor (L-NAME), or the neuronal-specific NO synthase inhibitor (7NI). Both NO inhibitors fully restored the CSN activity in response to hypoxia and hypercapnia in presence of EPO. Our results show that EPO activates the ventilatory response to hypoxia when its concentration does not exceed the threshold at which NO release from type I cells masks EPO’s action.